A coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers
By using diethylene glycol as a coagulant during the wet spinning process, combined with appropriate solvents, and controlling double diffusion, the fiber structure loose and low crystallinity caused by water polarity is solved, and the preparation of high-performance polyacrylonitrile raw silk is achieved. , reducing solvent consumption and production costs.
Patent Information
- Application Number
- CN202310073393.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The prior art During the wet spinning process, the polyacrylonitrile chain is too strong due to the strong polarity of water, which leads to loose structure of primary fibers, low crystallinity and high production costs. Increasing the solvent concentration will lead to insufficient diffusion power and fiber swelling. and adhesion.
Diethylene glycol is used as a coagulant, combined with dimethyl sulfoxide, NaSCN aqueous solution or ZnCl2 aqueous solution as solvent, to regulate the double diffusion rate, slow down phase separation, improve the homogenization and crystallinity of fibers, and reduce solvent consumption.
It effectively improves the homogenization and crystallinity of polyacrylonitrile protofilament, reduces the diffusion resistance of the coagulant, improves the mechanical properties of the fibers, and reduces production costs.
Smart Images

Figure CN116084034B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance carbon fiber precursor preparation, and specifically relates to a coagulation molding method for improving the homogenization and crystallinity of polyacrylonitrile primary fibers, which is used for preparing high-performance carbon fiber PAN precursor. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Carbon fiber has the advantages of high specific strength, high specific modulus, thermal conductivity, heat resistance, self-lubrication, etc. As an indispensable material, carbon fiber is widely used in the fields of automobiles, aerospace, biomedicine, renewable energy, building materials, etc.
[0004] During the wet spinning process, a thin stream of polyacrylonitrile enters the coagulation bath through the spinneret hole, and then double diffusion occurs, in which the solvent in the stock solution diffuses into the coagulation bath due to the concentration difference, and the coagulant in the coagulation bath diffuses into the stock solution. Finally, the stock solution thin stream reaches the critical concentration and spun fibers are precipitated. This process determines the homogeneity of the spun fibers. The faster the double diffusion speed, the stronger the interaction between the coagulant and the polyacrylonitrile chain, the easier it is to quickly form a dense structure in the cortex of the spun fibers, increasing the resistance of the coagulant to diffuse into the interior of the spun fibers, resulting in a loose internal structure of the spun fibers and a serious skin-core structure, and the structure is inherited by the carbon fibers. In addition, the stronger the interaction between the coagulant and the polyacrylonitrile chain, the greater the constraint on the polyacrylonitrile chain, so it cannot move freely to arrange and participate in crystallization, which ultimately causes the crystallinity of the spun fibers to decrease.
[0005] At present, the general technology uses water as a coagulant, but due to the strong polarity of water, it has a strong bond with the polyacrylonitrile chain, resulting in a violent phase separation. Therefore, the primary fibers are prone to holes and uneven texture. Increasing the concentration of the solvent to alleviate the degree of interaction between water and polyacrylonitrile chains in the coagulation bath will lead to insufficient diffusion power, causing the primary fibers to swell and adhere, and the overall structure is loose. In addition, considering the price of the solvent in the coagulation bath, increasing the proportion of the solvent in the coagulation bath will often increase production costs. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a coagulation molding method for improving the homogenization and crystallinity of polyacrylonitrile primary fibers, which can effectively slow down double diffusion and reduce the consumption of solvent, thereby obtaining high-performance polyacrylonitrile precursor and carbon fiber. In the wet spinning process, a coagulant is reasonably selected, which can reduce the solvent consumption while slowing down the violent phase separation caused by double diffusion and improving the crystallinity of the primary fibers, so that a homogeneous precursor with high mechanical strength can be prepared.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers comprises the following steps:
[0009] The polyacrylonitrile stock solution obtained by copolymerizing acrylonitrile and a comonomer is spun into a coagulation bath and drawn to obtain primary fibers;
[0010] The coagulation bath comprises a coagulant and a solvent, wherein the coagulant is diethylene glycol, and the solvent is selected from dimethyl sulfoxide, dimethylformamide, dimethylacetamide, acetone, a NaSCN aqueous solution or a ZnCl2 aqueous solution, and the mass percentage of the coagulant in the coagulation bath is 20%-80%;
[0011] The above solvents are the solvents for producing polyacrylonitrile precursor, and the solvent in the coagulation bath must match them.
[0012] The comonomer is selected from itaconic acid, sodium propylene sulfonate, sodium methpropylene sulfonate, methyl acrylate, methyl methacrylate, methacrylic acid or acrylamide.
[0013] The above comonomers have the advantage of a large spatial volume, so they can reduce the interaction between polyacrylonitrile molecular chains, thereby improving the elasticity of polyacrylonitrile fibers. In addition, the above comonomers can increase the degree of cyclization of polyacrylonitrile fibers, thereby making the fibers denser.
[0014] In the coagulation bath, the solvent in the polyacrylonitrile stock solution stream diffuses into the coagulation bath, and the coagulant in the coagulation bath diffuses into the stock solution stream. When the double diffusion reaches equilibrium, the stock solution stream reaches a critical concentration and precipitates.
[0015] In some embodiments, the temperature of the coagulation bath is 20-70° C. This coagulation temperature can achieve uniform coagulation of the fibers.
[0016] In some embodiments, the comonomer is itaconic acid. Itaconic acid has an active reaction property and is conducive to the cyclization process of polyacrylonitrile precursor during pre-oxidation.
[0017] In some embodiments, the solvent of the coagulation bath is dimethyl sulfoxide. Dimethyl sulfoxide has low toxicity.
[0018] In some embodiments, the linear velocity of the polyacrylonitrile stock solution after being sprayed out by spinning is 5-50 m / min.
[0019] In some embodiments, the draw ratio is between -10% and -100%.
[0020] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0021] The present invention replaces the coagulant water in the traditional coagulation bath with diethylene glycol, which reduces the interaction between the coagulant and the polyacrylonitrile chain molecules, allowing the polyacrylonitrile molecular chains to freely stack and participate in crystallization to a greater extent, thereby improving the crystallinity of the primary fiber. At the same time, the weak interaction between the coagulant and the polyacrylonitrile chain weakens the degree of phase separation, inhibits the formation of a dense cortical structure, reduces the diffusion resistance of the coagulant in the thin stream, ensures that the primary fiber obtained has a uniform structure from the inside to the outside, improves the skin-core structure, and thereby improves the mechanical properties of the polyacrylonitrile precursor.
[0022] In the coagulation bath, diethylene glycol enters the stock solution stream from the coagulation bath through double diffusion, regulating the precipitation rate of polyacrylonitrile. Compared with the commonly used coagulation bath with water as the coagulation agent, the polyacrylonitrile-two solvents-diethylene glycol ternary phase diagram has a larger metastable region. Since diethylene glycol has a smaller polarity than water, the diethylene glycol / polyacrylonitrile interaction parameter is smaller than the water / polyacrylonitrile interaction parameter.
[0023] Therefore, compared with water as a coagulant, diethylene glycol has less constraints on the polyacrylonitrile chain. On the one hand, it slows down the rapid coagulation and precipitation on the surface of the stock solution stream, which helps the coagulant diffuse into the interior of the stock solution stream, thereby facilitating the formation of homogeneous primary fibers. On the other hand, the effect of diethylene glycol on the polyacrylonitrile molecular chain is relatively weak, resulting in less entanglement between polyacrylonitrile molecules, which is conducive to the orderly movement of the molecular chain to participate in crystal growth.
[0024] When the mass percentage of diethylene glycol in the coagulation bath is 20-80%, the homogenization degree of the fiber can be better improved, while avoiding the looseness of the overall fiber structure caused by insufficient double diffusion power. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 Schematic diagram of wet spinning for preparing high-homogeneity and high-crystallinity spun fibers according to an embodiment of the present invention.
[0027] Among them, 1. spinneret; 2. coagulation bath; 3. nascent fiber; 4. guide disc. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Example 1
[0031] A coagulation molding method for improving the homogenization and crystallinity of polyacrylonitrile primary fibers, the preparation steps of which are as follows:
[0032] The polyacrylonitrile copolymer was obtained by solution polymerization. With acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent and azobisisobutyronitrile as initiator, free radical polymerization was carried out at 60°C to finally obtain acrylonitrile-itaconic acid binary copolymer with a comonomer ratio of 99:1. After 12 hours of de-monomerization and degassing, wet spinning can be carried out.
[0033] The polymer linear velocity of the spinneret is 20 m / min, the coagulation bath uses a mixed solution of dimethyl sulfoxide and diethylene glycol (mass ratio is 3:7), the coagulation bath draft is -25%, the residence time of the nascent fiber in the coagulation bath is 7 s, and the coagulation bath temperature is maintained at 30°C.
[0034] The spun fibers were washed, drawn, and dried to obtain polyacrylonitrile precursors. The obtained precursors had a tensile strength of 6.4 cN / Dtex. The dried spun fibers were shredded and ground into powders, and the powders were tested using a D / max-rc X-ray diffractometer, with a scanning interval of 5-50° and a scanning rate of 4° / min. The crystallinity C was calculated using the Hinrichen method, with the formula C=Ac / Ac+Aa, where Ac is the area of the diffraction peak in the crystalline region at 2θ≈17°, and Aa is the area of the diffraction peak in the amorphous region. The calculated crystallinity was 42.31%.
[0035] Example 2
[0036] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0037] The metering pump speed was adjusted, the polymer linear velocity of the spinneret hole was 25 m / min, and the other process parameters and steps were the same as those in Example 1. The calculated tensile strength of the raw fiber was 7.3 cN / Dtex, and the calculated crystallinity of the spun fiber was 47.85%.
[0038] Example 3
[0039] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0040] The metering pump speed was adjusted, the polymer linear velocity of the polymerization spinneret was 30 m / min, and the other process parameters and steps were the same as in Example 1. The calculated tensile strength of the raw fiber was 6.9 cN / Dtex, and the calculated crystallinity of the spun fiber was 46.35%.
[0041] Example 4
[0042] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0043] The coagulation bath used a mixed solution of dimethyl sulfoxide and diethylene glycol (the mass ratio was adjusted to 3.5:6.5), and the other process parameters and steps were the same as in Example 2. The calculated tensile strength of the raw fiber was 6.6 cN / Dtex, and the calculated crystallinity of the as-spun fiber was 43.72%.
[0044] Example 5
[0045] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0046] The coagulation bath used a mixed solution of dimethyl sulfoxide and diethylene glycol (the mass ratio was adjusted to 2:8), and the other process parameters and steps were the same as in Example 2. The calculated tensile strength of the raw fiber was 6.1 cN / Dtex, and the calculated crystallinity of the spun fiber was 44.34%.
[0047] Example 6
[0048] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0049] The coagulation bath quality is the same as that in Example 4, and the coagulation bath temperature is adjusted to 40° C. The other process parameters are the same as those in Example 2, and the calculated tensile strength of the raw fiber is 5.6 cN / Dtex, and the calculated crystallinity of the spun fiber is 40.04%.
[0050] Example 7
[0051] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0052] The coagulation bath temperature and quality are the same as those in Example 4, and the coagulation bath draft ratio is adjusted to -60%. The remaining process parameters and steps are the same as those in Example 2. The calculated tensile strength of the raw fiber is 5.5 cN / Dtex, and the calculated crystallinity of the nascent fiber is 39.01%.
[0053] Comparative Example 1
[0054] The polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60° C. using acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process was the same as in Example 1.
[0055] The coagulation bath used a mixed solution of dimethyl sulfoxide and water (mass ratio was 3:7), and the other process parameters and steps were the same as in Example 1. The calculated tensile strength of the raw fiber was 5.3 cN / Dtex, and the calculated crystallinity of the spun fiber was 35.51%.
[0056] Comparative Example 2
[0057] A polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60°C with acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process being the same as in Example 1. The coagulation bath was a mixed solution of dimethyl sulfoxide and water (the mass ratio was adjusted to 3:7), and the other process parameters and steps were the same as in Example 2. The calculated tensile strength of the raw fiber was 6.2 cN / Dtex, and the calculated crystallinity of the nascent fiber was 36.52%.
[0058] Comparative Example 3
[0059] A polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60°C with acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process being as in Example 1. The coagulation bath was a mixed solution of dimethyl sulfoxide and water (mass ratio being 3:7), and the other process parameters were as in Example 3. The calculated tensile strength of the raw fiber was 5.5 cN / Dtex, and the calculated crystallinity of the nascent fiber was 31.65%.
[0060] Comparative Example 4
[0061] A polyacrylonitrile copolymer was obtained by solution polymerization. With acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator, a free radical polymerization reaction was carried out at 60°C to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers was 99:1, and the polymerization process was as in Example 1. The coagulation bath used a mixed solution of dimethyl sulfoxide and water (mass ratio of 3.5:6.5), and the other process parameters were as in Example 4. The calculated tensile strength of the raw fiber was 5.8 cN / Dtex, and the calculated crystallinity of the nascent fiber was 40.31%.
[0062] Comparative Example 5
[0063] A polyacrylonitrile copolymer was obtained by solution polymerization. A free radical polymerization reaction was carried out at 60°C with acrylonitrile and itaconic acid as comonomers, dimethyl sulfoxide as solvent, and azobisisobutyronitrile as initiator to finally obtain an acrylonitrile-itaconic acid binary copolymer, the ratio of the comonomers being 99:1, and the polymerization process being as in Example 1. The coagulation bath was a mixed solution of dimethyl sulfoxide and water (mass ratio being 2:8), and the other process parameters were as in Example 5. The calculated tensile strength of the raw fiber was 5.1 cN / Dtex, and the calculated crystallinity of the nascent fiber was 41.48%.
[0064] Table 1 is a comparison table of the tensile strength of polyacrylonitrile precursor and the crystallinity of the as-spun fiber obtained in the examples and comparative examples.
[0065]
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A coagulation molding method for improving the homogenization and crystallinity of polyacrylonitrile primary fibers, characterized in that: The steps include: The polyacrylonitrile stock solution obtained by copolymerizing acrylonitrile and a comonomer is spun into a coagulation bath and drawn to obtain primary fibers; The coagulation bath comprises a coagulant and a solvent, wherein the coagulant is diethylene glycol, and the solvent is selected from dimethyl sulfoxide, dimethylformamide, dimethylacetamide, acetone, a NaSCN aqueous solution or a ZnCl2 aqueous solution, and the mass percentage of the coagulant in the coagulation bath is 20%-80%; The comonomer is selected from itaconic acid, sodium propylene sulfonate, sodium methpropylene sulfonate, methyl acrylate, methyl methacrylate, methacrylic acid or acrylamide; The linear speed of the polyacrylonitrile stock solution after being sprayed out by the spinneret is 5-50m / min; The temperature of the coagulation bath is 20-70°C; In the coagulation bath, diethylene glycol enters the stock solution stream from the coagulation bath through double diffusion, thereby regulating the precipitation rate of polyacrylonitrile.
2. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: The temperature of the coagulation bath is 30-60°C.
3. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: The comonomer is itaconic acid.
4. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: The solvent of the coagulation bath is dimethyl sulfoxide.
5. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: The linear velocity of the polyacrylonitrile stock solution after being sprayed out by the spinneret is 15-40m / min.
6. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: The draft ratio is -10% to -100%.
7. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 1, characterized in that: In the coagulation bath, the mass percentage of the coagulant is 30%-70%.
8. The coagulation molding method for improving homogenization and crystallinity of polyacrylonitrile primary fibers according to claim 7, characterized in that: In the coagulation bath, the mass percentage of the coagulant is 30%-60%.